Food loss and food waste assesment at the Instituto Tecnológico de Costa Rica - Rodríguez-Rodríguez, Alina (2021)
Roughly one-third of the food produced on the planet is lost or wasted like a consequence of poor cultivation techniques and consumer-related behavioral factors. This situation generates important repercussions on the environment, the economy and society, especially in regions that its feeding depends on imports. In response, nations around the world have devised different policies to decrease waste and increase food security for their inhabitants. In the case of Costa Rica, the “Red costarricense para la reducción de la pérdida y el desperdicio de alimentos” was created in 2014 with the objective of design strategies to minimize losses and waste in the country. This is how in 2018, the Costa Rican Institute of Technological joins the national efforts to perform an evaluation in the Institutional Restaurant of the Central Technological Campus on the amount of food discarded during its storage, preparation, and consumption. Results indicate that 927,75 kg of organic waste are generated during a teaching week, of which 55% are discarded resulting of food loss and waste. In this way, it was determined that 9.56% of produced food is discarded. These data are part of a baseline, from which the application of new strategies that improve food management in the Institution will be evaluated.